Potential applications of N6‐methyladenosine modification in the prognosis and treatment of cancers via modulating apoptosis, autophagy, and ferroptosis. (3rd February 2022) - Zhi, Yuan; Zhang, Shanshan; Zi, Moxin; Wang, Yian; Liu, Yuhang; Zhang, Mi; Shi, Lei; Yan, Qijia; Zeng, Zhaoyang; Xiong, Wei; Zhi, Keqian; Gong, Zhaojian
Abstract: N 6 ‐methyladenosine (m 6 A) is one of the most abundant modifications determining the fate of RNA. Currently, m 6 A modification is tightly connected with tumorigenesis and presents novel promise in clinical applications. Regulated cell death (RCD) is a programmed mechanism that plays a complicated role in malignant transition. Regarding the main forms of RCD, aberrant levels of m 6 A modification have been detected during the progression of apoptosis, autophagy, ferroptosis, necroptosis, and pyroptosis in several diseases. However, few reviews have elucidated the correlation between m 6 A‐modified RCD and carcinogenesis. In this review, we summarize the regulators of m 6 A methylation and their functions in carcinogenesis through an overview of m 6 A‐modified RCD. Additionally, we assume the potential role of m 6 A modification regulators as novel biomarkers for chemotherapies and precision medicine. Furthermore, we review the controversies and conflicts in m 6 A explorations and predict future orientations of m 6 A‐modified RCD for clinical applications. This article is categorized under: Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs Abstract : Role of m 6 A Modification in Biological Processes.